PELATIHAN KEGIATAN UNTUK MEMBANGUN BUDAYA LITERASI MELALUI POJOK BACA (POCA) DI SDN GANDRI 2 - Alyatiko Salsabila; Nabilla Dwi Alisa; Alfian Nur Huda Pratama; Dewi Tryanasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy culture plays an important role in supporting the success of learning in elementary schools. However, based on conditions in the field, students’ reading interest still needs to be improved due to limited reading facilities and the lack of regular reading habits. This issue was also found at SDN Gandri 2, Pangkur District, Ngawi Regency, where literacy activities had not been optimally implemented. This community service activity aimed to improve students’ literacy culture and reading interest through the implementation of a Reading Corner (POCA) in the classroom. The activity employed a qualitative descriptive approach conducted through stages of observation, planning, implementation, mentoring, and evaluation. The participants were eight second-grade students of SDN Gandri 2, accompanied by KKN-T Berdampak students from Universitas PGRI Madiun and the classroom teacher. Data were collected through observation during the activity and analyzed based on program implementation indicators. The results showed an increase in students’ use of the reading corner, higher participation in reading activities, and positive responses and enthusiasm toward literacy activities. In addition, the classroom teacher continued to utilize the reading corner as part of daily learning activities. Based on these findings, it can be concluded that the implementation of the Reading Corner (POCA) serves as an effective alternative to foster reading habits and strengthen literacy culture in elementary schools.